Study of the surface glycoprotein of Rift Valley fever virus using monoclonal antibodies - Besselaar, Terry Gail (My University, 2016)
The structural, functional and antigenic properties of the envelope glycoproteins of Rift Valley fever virus (RVFV) were analyzed using a panel of monoclonal antibodies (MAbs). In order to gain a better understanding of the role of the RVFV surface proteins in infection and pathogenesis, the mechanisms ofanti:~odymediated neutralization of the virus were examined, as well as the fl}action of the glycoproteins in viral attachment and penetration. Of the twenty three MAbs which were generated, fourteen were directed against the G1 and nine against the G2 protein of RVFV. The topological relationship of the antigenic determinants to each other on the viral glycoproteins was achieved using competitive binding assays with enzyme-labelled MAbs. For the RVFV 01 protein, four antigenic domains which may be interlinked were identified. The domains G1 I, II and IV were involved in virus neutralization and haemagglutination, while G1 III was associated with low level C'-dependent neutralization. With regard to the G2 protein, four antigenic domains which appear to be spatially distinct were identified. Domain G2 I exhibited significant neutralizing and haemagglutination activity, while G2 II was involved in haernagglutination and weak C(-dependent neutralization. The remaining 02 regions neutralized to a low level only in the presence of C'. The majority of the epitopes on bath viral glycoproteins were highly conformational, indicating that the native protein structure is necessary for the recognition and expression of the functional activities of these particular antibodies. Protective determinants were shown to occur on both Gland 02, demonstrating that both RVFV envelope proteins are important in viral pathogenesis. The neutralization studies, in turn, revealed that the inhibition of virus attachment is not the principal means of antibody-mediated neutralization of RVFV. Instead, such ..ieutralization appears to be the result of several different processes, including synergistic neutralization by combinations of different antibodies, prevention of virus binding, virus internalization and the blocking of the viral life cycle at an intracellular stage. Further insight into RVFV infectivity was obtained by showing that both glycoproteins are involved in virus entry into the host cell. Finally, the present. findings strongly support an endosomal route of entry and penetration for RVFV, associated with concomitant allosteric changes in the 01 protein.
A thesis submitted to the Faculty of Medicine University of the Witwatersrand, Johannesburg for the De +ee of Doctor of Philosophy Johannesburg, 1992